Teledentistry actions in Primary Healthcare during the COVID-19 pandemic: cross-sectional study, Brazil, 2021 - Mariane Baltassare Laroque; Thais Freitas Formozo Tillmann; Bruna Vettorazzi Liskoski; Alexandre Emidio Ribeiro Silva (Epidemiologia e Serviços de Saúde)
Abstract Objective To analyze the use of teledentistry in Primary Healthcare in Brazil at the end of the second year of the COVID-19 pandemic. Methods Cross-sectional study with dentists and dental surgeons in Primary Healthcare. Study data were obtained through an online form. The outcome was the use of teledentistry in Basic Health Units. The exposure variables were related to dentists, municipalities and the adoption of protocols by the municipality to reduce the risk of COVID-19. Descriptive and bivariate analyses were performed, and finally, adjusted regression analysis was performed, in which prevalence ratios (PR) and 95% confidence intervals (95%CI) were obtained. Results 416 dentists were evaluated. Of these, 24.3% reported using teledentistry, with remote guidance being the most used modality (85.6%). The highest probability of implementing teledentistry occurred in Basic Health Units in the South (RP 4.20; 95%CI 1.71; 10.28) and Southeast (RP 6.85; 95%CI 2.74; 17.67) regions of Brazil, which adopted protocols to reduce the risk of COVID-19 (PR 1.59; 95%CI 1.01; 2.50) and had dentists specialized in Public/Collective Health (PR 2.12; 95%CI 1.20; 3.75). Conclusion Limited use of teledentistry was observed by Basic Health Units in Brazil. Factors related to the adoption of protocols to reduce the risk of COVID-19, the Brazilian region of the Basic Health Unit and the presence of a dentist with specialization in Public/Collective Health were positively associated with the implementation of teledentistry.